Polymorph of 4-(carbazol-9-yl)benzonitrile - Xie, Yu-Zhong (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(19)H(12)N(2), contains two independent molecules with a similar structure. In the two molecules, the dihedral angles between the carbazole ring system and the benzene ring are 47.9 (5) and 45.4 (4)°, similar to the value of 47.89 (6)° found in the previously reported structure [Saha & Samanta (1999 ▶). Acta Cryst. C55, 1299–1300]. In the crystal, there is a weak C—H⋯N hydrogen bond between the two independent molecules.